2022
DOI: 10.1038/s41528-022-00175-7
|View full text |Cite
|
Sign up to set email alerts
|

A ternary heterogeneous hydrogel with strength elements for resilient, self-healing, and recyclable epidermal electronics

Abstract: Epidermal sensing devices, which mimic functionalities and mechanical properties of natural skin, offer great potential for real-time health monitoring via continuous checking of vital signs. However, most existing skin-mounted electronics use a flexible film with high elastic modulus, which hinders physical activity and causes interfacial delamination and skin irritation. The compliance of hydrogel-based devices can firmly conform to complex, curved surfaces without introducing excessive interfacial stresses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…The development of conductive and robust hydrogels for use in bioelectronics, including tactile and strain sensors, electronic skin, and physiologic signal monitoring, has been a major focus of research. To satisfy the requirements of biocompatibility, biostability, high electrochemical conductivity, and mechanical stability, numerous studies have been conducted. ,, In this study, we confirmed the biocompatibility of LMCs through live/dead cell staining (Figure a). Immunofluorescence images verified that 3T3 cells cultured for 1 and 3 days with PCH and LMC5 displayed sparse dead cells (red) and little difference compared to the control.…”
Section: Resultssupporting
confidence: 63%
“…The development of conductive and robust hydrogels for use in bioelectronics, including tactile and strain sensors, electronic skin, and physiologic signal monitoring, has been a major focus of research. To satisfy the requirements of biocompatibility, biostability, high electrochemical conductivity, and mechanical stability, numerous studies have been conducted. ,, In this study, we confirmed the biocompatibility of LMCs through live/dead cell staining (Figure a). Immunofluorescence images verified that 3T3 cells cultured for 1 and 3 days with PCH and LMC5 displayed sparse dead cells (red) and little difference compared to the control.…”
Section: Resultssupporting
confidence: 63%
“…Therefore, to apply bioelectronics to the skin, there are only a few requirements (e.g., sweat‐resistance, air‐permeable, elastic, flexible, and stretchable), and most failures do not cause serious problems for the user 202 . Compared to bioelectronics applied to internal organs, those applied to skin have simple functions (e.g., electrophysiological monitoring, drug delivery, epidermal chemistry monitoring, and wound healing) 203 and potential to decrease pollution by using bioelectronics systems (e.g., charged by actions without battery, 202 natural hydrogels, 203 recyclable epidermal electronics, 204 and starch‐based materials 205 ). However, although the operations (e.g., breathable conductive modeling, dermis insertion, epidermal combined electronics, and multichannel measuring) 206 and electronics (e.g., electrophysiological sensor, conductive microneedles, and photothermal electronic patch) 207 of bioelectronics applied to the skin are low‐risk, we can obtain many functions from skin‐on bioelectronics from various approaches 207 .…”
Section: Wearable and Implantable Bioelectronic Systems For Smart Hea...mentioning
confidence: 99%
“…Cui et al constructed a double network nanocomposite hydrogels sensor with high strength (1.2 MPa) by incorporating tannic acid-coated cellulose nanocrystals (TA@CNC) as nanofillers into a chitosan-based conductive hydrogel, highlighting the NaCl solution immersion method (the mechanical properties of the hydrogel easily tuned by varying the immersion time). Additionally, Wang et al prepared biomass conductive hydrogels with three-dimensional interconnected porous network microstructures by a dual-network, dual-cross-linking process (Figure A). They employed PVA hydrogel with adjustable modulus as a model material system, restructured the polymer matrix of embedded hydroxypropyl cellulose (HPC) and conductive carbon nanotubes (CNTs), which were applied to enhance their mechanical and electrical properties, respectively; further cross-linked the existing PVA molecular chains in the aqueous system of HPC/CNTs with the chemical cross-linking agent, sodium tetraborate, to form an elastic PVA hydrogel; and increased the crystallinity of the PVA hydrogels by introducing a freeze–thaw physical cross-linking procedure, which protected the integrity of the network, improved the fatigue fracture resistance threshold, and consolidated the self-healing properties.…”
Section: Sensing Functionsmentioning
confidence: 99%
“…(A) (i) Mechanistic schematic of the ternary strength elements of PVA-S hydrogels, (ii) conducive strength of the PVA-S hydrogel: stretching, lifting test with a load of 1.5 kg, and in-plane extension, and (iii) tensile stress–strain curves of representative PVA-S hydrogels. Reproduced with permission from ref . Copyright 2022 Nature Publishing Group.…”
Section: Sensing Functionsmentioning
confidence: 99%
See 1 more Smart Citation